Islamisasi Demokrasi: Telaah Kritis Atas Teori Mayoritas Hans Kelsen - Savier Nayaka Gunawardana; Muhammad Rafi Dhiaulhaq Sasongko (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2025)
Abstract: This research is motivated by the dominance of democracy in modern state governance, particularly the principle of majority rule as developed by Hans Kelsen. Although considered a solution to social anarchy, this principle is vulnerable to marginalizing minority groups and opens the door to abuse of power. The aim of this study is to critically examine Kelsen’s theory of majority rule from an Islamic perspective, by analyzing the thoughts of Muslim scholars such as Abbas Mahmud Al-Aqqad and Syed Naquib Al-Attas. The method used is qualitative with a library research approach, relying on both classical and contemporary literature sources. The study aims to critique Kelsen’s theory of majority rule through the lens of Islamic thought. The findings show that the principle of majority is not always synonymous with justice in Islam. The Qur’an often warns of misguidance that can be supported by the majority. Islam places greater emphasis on consultation (shura) involving those who are knowledgeable (ahlul halli wal ‘aqdi) and on the implementation of sharia as the foundation of law. Additionally, the concept of ta’dib (education in adab or moral discipline) is seen as a fundamental solution to building a just and civilized society. In conclusion, the democratic principle of majority rule needs to be Islamized in order to remain aligned with divine values and to ensure it does not contradict the Islamic concept of justice.Keywords: Hans Kelsen, islamic critique, majority principle.Abstrak: Penelitian ini dilatarbelakangi oleh dominasi sistem demokrasi dalam tata kelola negara modern, khususnya pada prinsip suara terbanyak yang dikembangkan oleh Hans Kelsen. Meskipun dianggap sebagai solusi atas anarkisme sosial, prinsip ini rentan menyebabkan marginalisasi terhadap kelompok minoritas dan membuka celah penyalahgunaan kekuasaan. Tujuan dari penelitian ini adalah untuk mengkritisi teori suara terbanyak Kelsen melalui perspektif Islam, dengan menelaah pemikiran para cendekiawan muslim seperti Abbas Mahmud Al-Aqqad dan Syekh Naquib Al-Attas. Metode yang digunakan adalah kualitatif dengan pendekatan studi pustaka, yang mengandalkan sumber-sumber literatur klasik dan kontemporer. Penelitian ini bertujuan mengkritisi teori suara terbanyak Kelsen melalui pendekatan pemikiran Islam. Hasil penelitian menunjukkan bahwa prinsip mayoritas tidak selalu identik dengan keadilan menurut Islam. Al-Qur’an bahkan sering memperingatkan tentang kesesatan yang didukung oleh mayoritas. Islam lebih menekankan musyawarah oleh orang-orang berilmu (ahlul halli wal ‘aqdi) dan pelaksanaan syariat sebagai dasar hukum. Selain itu, pendidikan adab (ta’dib) dianggap sebagai solusi fundamental untuk membentuk masyarakat adil dan berkeadaban. Kesimpulannya, prinsip demokrasi dalam bentuk suara terbanyak perlu diislamisasi agar tetap sejalan dengan nilai-nilai wahyu dan tidak bertentangan dengan prinsip keadilan dalam Islam.Kata kunci: Hans Kelsen, Kritik Islam, Prinsip Mayoritas.